The REAP-HOTS Model: A Multi-Level Framework for Developing Higher-Order Thinking Skills in Philippine Rural Elementary Schools - Damoco, Teofilo B (Technium Education and Humanities, 2026)
The development of higher-order thinking skills (HOTS) remains a paramount educational objective worldwide, yet its realization in resource-constrained and geographically isolated rural settings continues to face formidable systemic, pedagogical, and sociocultural barriers. This study introduces the REAP-HOTS Model, a multi-level, context-sensitive framework specifically designed to guide the cultivation of HOTS in Philippine rural elementary schools. Employing a methodologically rigorous systematic review that adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, the research synthesized evidence from 150 global studies and 111 Philippine-localized studies spanning empirical investigations, policy evaluations, and theoretical expositions published between 2005 and 2026. The resulting framework delineates four deeply interdependent and recursively interactive layers: the Systemic and Community Layer, the Professional Capacity Layer, the Pedagogical Practice Layer, and the Rural Learner Layer. Grounded in Bronfenbrenner's Ecological Systems Theory, Vygotsky's Social Constructivism, and Freire's Critical Pedagogy, the model demonstrates that effective HOTS cultivation demands systemic coherence, culturally responsive pedagogies that leverage indigenous knowledge systems and linguistic pluralism, sustained transformative professional development for educators, and holistic attention to learner cognitive, affective, and socio-emotional needs. The study further proposes a phased five-year district-level implementation roadmap, providing policymakers, curriculum designers, school leaders, and educators with an actionable and evidence-based blueprint to operationalize equitable cognitive skill development. By foregrounding the unique sociocultural realities of marginalized rural learners, the REAP-HOTS Model offers a comprehensive, glocalized pathway to transform rural educational landscapes into enabling environments that empower Filipino children for critical thinking, lifelong learning, and meaningful civic participation.